Developing Instructional Book of English for Theologys Students, at Faculty of Theology, Indonesia Christian University of Toraja - Nehru P. Pongsapan (Teaching English as a Foreign Language Overseas Journal, 2017)
English for Theology is conducted as English for Specific purposes (ESP) becausethis course focuses on aspects of English related to the study of theology, includingtheological terms. Pierson et al (2010b) classify English for Theology into Englishfor Academic Purposes (EAP). EAP course is generally for students who arelearning in a classroom or another academic setting. English for Theology courseis categorized into EAP because most students require this knowledge foracademic purposes.In applying English for Theology (ET) course at Theology faculty, the students inthis institution encountered the difficulty when they learn this course. Instructionaldesign is a systematic process that is employed to develop education and trainingprograms in a consistent and reliable fashion. However, instructional design is acomplex process that is creative, active, and interactive. ADDIE illustrates theconceptual components of instructional design. Instructional design modelsindicate how to practice instructional design. Instructional design models allowpeople to visualize the overall process and establish guidelines for managinginstructional design processes. Instructional design provides a means forcommunicating among team members, clients, and stakeholders.The topics and subtopics which compossed as the contents of instructional book forEnglish for thfor Theology Course are:1. Prayer : Lord’s Prayer and Classroom Prayer2. Holy Bible : Books of the Old Testament and Books of the NewTestament3. God : The nature of God and The Attributes of God4. Jesus Christ : The person of Christ and The work of Christ5. Holy Spirit: The work of Holy Spirit and The names of Holy Spirit6. Man : The creation of man and The fall of man7. Church : Worship, Sacrament, Tools and parts of the church andMembership in the church8. Salvation : Repentance and Faith9. Last Things : The second coming of Christ and Judgement10. The Prophets and The Apostles : The Prophets and The Apostles